Analisis Ketimpangan Pembangunan Antarkabupaten/Kota di Provinsi Nusa Tenggara Timur Tahun 2021-2024 - Chandra Rinaldy Mbura; Christian Putra Ginting (Badan Pusat Statistik Provinsi NTT, 2025)
One of the key missions outlined in the Asta Cita of Indonesia's President and Vice President is achieving equitable development. However, Nusa Tenggara Timur (NTT) remains a province facing significant challenges in this regard. This study analyzes development inequality across regencies and municipalities in NTT from 2021 to 2024, using the Bonet index as a measure of regional disparity. Descriptive analysis, based on variance and mean values of the Bonet index, shows a tendency toward increasing inequality during the period. Additionally, boxplot analysis reveals that Kupang Municipality consistently stands as an outlier, indicating its development level is significantly higher than that of other districts in NTT. Panel data regression analysis shows that variables such as the Human Development Index (HDI), Open Unemployment Rate (TPT), and the growth rate of the primary sector have a positive and significant impact on regional disparity, while capital expenditure does not significantly affect regional disparity. Based on these findings, it is recommended that the NTT provincial government prioritize equitable human development, targeted unemployment reduction, economic diversification, and optimize capital expenditure for the purpose of balanced regional development.